Corporate social responsibility, discussion elements (2019)
This article shows the discussion around how to establish the grade for corporatesocial responsibility of a company. Concepts arise to evaluate if the activitiesdeveloped as corporate social responsibility are enough still not having framed ina defined program from the corporate strategy. The review was conducted withdifferent documents published by different authors, specialists in the subjectand found that companies socially responsible, need to be enrolled with laborrights for workers, the welfare of communities and to advance in preservationprograms for the environment to contribute sustainable development.